Cytokines induce effector T-helper cells during invasive aspergillosis; what we have learned about T-helper cells? - Thakur, Raman; Anand, Rajesh; Tiwari, Shraddha; Singh, Agam P.; Tiwary, Bhupendra N.; Shankar, Jata (Frontiers in Microbiology, 2015)
Invasive aspergillosis caused by Aspergillus species (Aspergillus fumigatus, A. flavus and A. terreus) is life-threatening infections in immunocompromised patients. Understanding the innate and adaptive immune response particularly T-helper cells (TH-cells) against these Aspergillus species and how the different sub-set of TH-cells are regulated by differentiating cytokines at primary target organ site like lung, kidney and brain is of great significance to human health. This review focuses on presentation of Aspergillus through Antigen presenting cells (APCs) to the naive CD4+ T-cells in the host. The production of differentiating/effector cytokines that activate following TH-cells e.g., TH1, TH2, TH9 and TH17 has been reported in association or alone in allergic or invasive aspergillosis. Chemokines (CXCL1, CXCL2, CCL1 and CCL20) and their receptors associated to these TH-cells have also been observed in invasive aspergillosis. Thus, further study of these TH-cells in invasive aspergillosis and other elements of adaptive immune response with Aspergillus species are required in order to have a better understanding of host response for safer and effective therapeutic outcome.